Simulação da germinação e emergência de Ipomoea grandifolia na cultura de soja, usando o modelo ecofisiológico LQSIM Emerge - Luiz, Ana Rubia Marques (2006)
The use of herbicides is the main practice used for weed control on the most important grain production systems in Southern Brazil. The development of weed management systems with reduced dependence on herbicides is not only a society requirement but also a challenge for food production. The herbicides application when most of the weed have emerged is a strategy for the management of those species aiming at the reduction of herbicide application. This work have the objective of validating a ecophysiological model for predicting the phenology of emergence of (Ipomoea grandifolia Dommer O Donell.), as a function of the weather conditions on soybeans capable of assisting technicians and farmers on decision making in relation to herbicide application on soybeans. Studies were conducted under both field conditions and using Ipomoea grandifolia the germination process was described by the interaction of temperature and water potential white the rate of radicle and hypocotyl elongation was a function of temperature solely. The parameters for the model cardinal temperatures and base, water potential, were estimated by probit analysis. The parameters necessaries for the process of elongation, i.e. cardinal temperatures, was estimated by regression analysis and their reponse to temperature were describe by a second onder equation. The mathematical models described the processes of germination and radicle and hypocotyls elongation interms of thermal time respectively. The parameters obtained in the study were used in the LQSIM EMERGE which was validated using the data obtained under field conditions and can be used for predicting germination and emergence of Ipomoea grandifolia in the field